Porphyrin‐Based Metal–Organic Frameworks for Neuromorphic Electronics. Issue 2 (27th October 2022) - Ding, Guanglong; Han, Su-Ting; Kuo, Chi-Ching; Roy, Vellaisamy A. L.; Zhou, Ye
Abstract : Porphyrin‐based metal–organic frameworks (PP‐MOFs) have some special features beyond ordinary MOFs, including superior optoelectronic characteristics, the ability to form 2D layered structure, and customizability, which prompt the increasing attention of PP‐MOFs in the field of neuromorphic electronics. The related application research is in the initial stage, and a timely summary and guidance are necessary. The PP‐MOFs fabrication should be shifted from powder synthesis in a chemistry laboratory to high‐quality film preparation under a clean environment to ensure device performance. This article highlights the PP‐MOFs film preparation methods and the application advances in neuromorphic electronics, performs comparative analysis in detail, and puts forward the challenges and future research directions, with the aim to attract the attention of experts in various areas (e.g., chemists, materials scientists, and engineers) and promote the application of PP‐MOFs in neuromorphic electronics. Abstract : Porphyrin‐based metal–organic frameworks (PP‐MOFs) have superior optoelectronic characteristics, the ability to form 2D layered structure, and customizability, prompting the increasing attention in brain‐like device areas. This article highlights the PP‐MOFs film preparation methods and the application advances in brain‐like devices, performs comparative analysis in detail, and puts forward the challenges and future research directions.